Knowledge and self-reported practice of people living with Human immunodeficiency virus, with regard to antiretroviral therapy (ART) in Mangalore, India - Sonia Sequera; Irene TR Alvares (Wolters Kluwer Medknow Publications, 2015)
Context: The goal of universal access to antiretroviral therapy (ART) by 2010 was set at 80%, but most countries could not meet the target. In 2011, the international community recommitted the goal of universal access to ART by 2015. The Millennium Development Goal included halting and beginning to reverse the spread of human immunodeficiency virus (HIV) by 2015. Aim: To assess the knowledge and self-reported practice with regard to ART among HIV-positive people, to find the relationship between the knowledge and self reported practice, to find the relationship between knowledge and self-reported practice and to associate the knowledge and practice with the selected demographic data. Setting and Design: The ART Centre, Mangalore, descriptive correlational survey design. Materials and Methods: A Structured Interview Schedule on 60 patients who were on ART for >2 months. Statistical Analysis: Frequency, Mean, SD, mean percentage, Karl Pearson's Correlation Coefficient, and Chi-square for association. Result: The majority (78.3%) had good knowledge, 15% had very good knowledge, and a few had average knowledge (6.6%). Most had a safe practice 76.7%) and a few had a very safe practice (23.3%). The Karl Pearson's correlation coefficient ((r = 0.22), P value (0.82) > 0.05 level) revealed no significant correlation. Association was found between the knowledge level and type of family and reason for HIV testing. Conclusion: Pooled results showed that the overall knowledge and ART practice were good and safe.